F2RL3 Methylation in the Peripheral Blood as a Potential Marker for the Detection of Coronary Heart Disease: A Case-Control Study - Zhao, Xiaojing; Zhu, Liya; Yin, Qiming; Xu, Zhenguo; Jia, Qian; Yang, Rongxi; He, Kunlun (Frontiers in Genetics, 2022)
Background and Aims: Previous work has shown the association between blood-based methylation of coagulation factor II receptor-like 3 gene (F2RL3) and cardiovascular mortality in Caucasians. However, the diagnostic value of F2RL3 methylation for CHD is still unknown. The aim of our study was to evaluate the association between blood-based F2RL3 methylation and the risk of CHD in the Chinese population. Methods: The methylation level of F2RL3 was quantified by mass spectrometry in a case-control study with 180 CHD cases and 184 controls. The association between F2RL3 methylation intensity and CHD was assessed by logistic regression models, controlling confounding factors. Results: The hypomethylation in F2RL3_A amplicon was significantly associated with CHD (odds ratio (ORs) per -10% methylation: 1.22 - 1.42, p < 0.035 for six out of seven CpG loci). Specifically, this significant association was observed in elderly CHD patients (≥ 60 years), myocardial infarction (MI) patients, heart failure patients and the patients with minor to medium cardiac function impairment (NYHA Ⅰ&Ⅱ CHD cases) (ORs per -10% methylation: 1.35-1.58, 1.32-2.00, 1.29-1.43, 1.25-1.44; p < 0.024, 0.033, 0.035, 0.025, respectively). However, F2RL3_B CpG sites showed no or very weak association with CHD. The combination of F2RL3_A_CpG_1 and F2RL3_A_CpG_3 methylation levels could efficiently discriminate CHD, MI, heart failure, NYHA I&II CHD, and elderly CHD patients from controls (area under curve (AUC) = 0.75, 0.79, 0.75, 0.76, and 0.82, respectively). Conclusions: We propose blood-based F2RL3 methylation as a potential biomarker for CHD, especially for people with older age or with the status of MI. The combination of F2RL3 methylation and conventional risk factors might be an approach to evaluate CHD at early stage.